SISTEM REGISTRASI DAN MONITORING KERJA PRAKTEK PROGRAM STUDI TEKNIK INFORMATIKA - Insan, Alin Ghifaril (Jurusan Informatika Universitas Tanjungpura, 2014)
One of the subject that must be takenby the informatics Engineering of TanjungpuraUniversity student is the Internship Program.Internship program allows students to apply theknowledge that has been gained in lectures to theenvironmental community. To be able to dopracticum the students must register and submitthe internship program petition. If the internshipprogram petition is approved, students can startdoing their internship work. At the time of theinternship of guidance, tutoring students andlecturers are usually done with face-to-faceprocess. These methods are rather effective butstill have the constraints of time and place.On theimplementation of internship program, allprocesses from initial registration, guidance andseminars is one interconnected process. Web-based online information system will be needed tobe able to connect all the processes in thepracticum so that it would provide more ease andconvenience for students, faculty and staff toaccess the information of internship program.Therefore, web-based designed that using onlineinformation system, which can be an alternative atthe time of the internship guidance. In addition tothe guidance, the system also provides the featureto register the internship program and internshipseminar so students can sign up from anywhereand anytime. The Registration Data can also bedirectly accessed by the staff of InformaticsEngineering. Another feature that provide in web-based information service of monitoring andregistration system are SMS Gateway which isuseful to send a warning message if students andlecturers have not taken the guidance of morethan 7 days. With the establishment of theregistration and monitoring system of internshipprogram, guidance process not only can be doneby meeting directly but can also be done with theguidance online through the system.